Perception of voice alterations by persons with Parkinson’s disease - Jara Cabrera, Gerson; Farías , Patricia (Revista de Investigación en Logopedia, 2023)
The purpose of this work is to explore and identify perceptions about voice and speech difficulties in patients with Parkinson’s disease. For this, a qualitative study with a phenomenological approach was carried out. The sample consisted of 15 participants and the information was obtained through a semi-structured interview, which was recorded using a digital voice recorder and then transcribed for thematic analysis. The study has the consent of each of the interviewees and the approval of the ethics committee. From the analysis of the data, 4 categories emerged: knowledge about the affectation of the voice and speech in the disease, progression of the vocal symptomatology, affectation of the quality of life and coping with voice difficulties. All the participants consider that the voice and speech are affected as a result of the disease. The older subjects show greater difficulties, which would be related to the greater number of years of evolution of the disease. Due to these difficulties, the vast majority have gradually become more introverted, impacting this in different areas of their lives. In conclusion, people with Parkinson’s disease experience voice and speech impairment to varying degrees, affecting their work, social and family life, which is generating withdrawal and frustration. Positive coping and being able to share with other PD patients is a powerful tool for coping with the disease.